Interactive Media-Based Transformation of Islamic Religious Education and Character Learning: Integrating Digital Literacy and Islamic Value Internalization - Syarifudin (Lembaga Bale Literasi, 2025)
Educational digitalization requires Islamic Religious Education and Character Learning not only to preserve its value-oriented mission but also to utilize interactive media to strengthen students’ participation and understanding. This study aims to analyze the use of interactive learning media in Islamic Religious Education and Character Learning at SMA Islam Al-Azhar NW Kayangan and to identify the supporting and inhibiting factors in its implementation. It employed a descriptive qualitative approach through observation, interviews, and documentation. The data were analyzed inductively through data reduction, data display, and conclusion drawing. The findings reveal that interactive media use involves four stages: teacher preparation, media selection based on learning objectives and material characteristics, conditional media presentation, and follow-up activities through assignments, questions and answers, and reinforcement. The media used remain dominated by audio and visual forms, such as Qur’anic texts, textbooks, student worksheets, projection devices, and presentation materials, while the use of digital interactive applications is not yet evenly implemented. Interactive media contribute to students’ attention, enthusiasm, and participation, especially when integrated with lectures, discussions, question-and-answer activities, recitation assignments, and peer tutoring. However, implementation is constrained by unequal infrastructure, limited instructional time, uneven teacher digital competence, and varied student access to devices. This study proposes the concept of Islamic value-based digital pedagogy, namely the use of interactive media that goes beyond technological attractiveness and is directed toward value internalization, character formation, and religious digital literacy